The Role of Rational Emotive Behavior Therapy (REBT) in Increasing the Self-Esteem of Female Prisoners - Imaduddin Hamzah (HM Publisher, 2022)
The experience of women being prisoners causes a decrease in self-esteem (self-esteem). Various studies have found that low self-esteem is associated with anxiety, depression, and suicide. This condition can worsen the mental health of female prisoners while in prison. Cognitive behavior therapy (CBT) is a treatment method that has been widely applied to psychological problems such as depression and suicide. This study aimed to identify the effects of CBT with rational emotive behavior therapy (REBT) on increasing the self-esteem of female prisoners. The study used the experimental method of giving REBT for five sessions to twelve female prisoners by using the measurement Rosenberg self-esteem scale (RSES). The results of the study showed an average increase in self-esteem research subjects before and after the intervention of rational emotive behavior therapy (p<0.05). This research shows the potential of REBT to improve the mental health of female prisoners.